Clinical outcomes of dental implants placed in fresh sockets: A five-year retrospective study - Roohollah Naseri; Sepideh Asadollahi; Mohammadjavad Shirani; Narges Pouremadi (Saudi Dental Journal)
Purpose: This retrospective clinical study aimed to evaluate the implants placed in fresh sockets and investigate the effect of varied oral health conditions and treatment plan details on the clinical and radiographic outcomes. Materials and methods: Fifty-nine participants (102 implants) were included in this study. Four variables, including mean probing depth (PD), mean marginal bone loss (MBL), pink esthetic score (PES), and patient satisfaction, were significant dependent variables, and the effects of independent variables on these four items were studied. The data were analyzed by the analysis of covariance (ANCOVA) using a statistical software. Results: The mean follow-up period was 4.75 ± 1.74 years, and the mean MBL was 1.21 ± 0.81 mm. The survival rate was 97 %. There were significant effects of the finish line site, keratinized gingival width, and attached gingival width on PD after adjusting the factors. Also, the implant brand, plaque index, and uncemented prosthesis affected MBL significantly. In addition, significant effects of the surgeon, implant brand, and proximal contact on PES were found. Conclusion: More PD was found around restorations with a finish line site > 1.5 mm subgingival. Sufficient attached gingiva was a more effective factor on PD than keratinized gingiva. Implants with more plaque scores showed more MBL.